The Role of Social Studies Learning in Forming Responsible Character for Muhammadiyah Primary School Students 25 - Zakira; Sagita, Nesa (Berpusi Publishing, 2024)
This research aims to: (1) determine the role of a teacher as an educator and instructor. (2) knowing the social attitudes of Muhammadiyah Elementary School students 25. (3) knowing the responsibilities of students. (4) knowing the big influence that social studies teachers have in developing social sciences for all Muhammadiyah 25 Elementary School students. Data analysis for this research collects simple linear regression analysis. The results of the research show: (1) the conflicting role of social studies teachers as teacher educators. (2) the contribution of students' social attitudes that are developed in school. (3) contribution of responsible attitudes from each student. (4) the contribution of the great influence given by the social studies teacher to Muhammadiyah 25 Elementary School students. This study aim for know the influence of an educator in social studies learning SDS Muhammadiyah 25. This research uses a descriptive qualitative approach. Data collection techniques were carried out through literacy, interviews, and technology data sources. Social studies learning has an important role in everyday life and is very important in forming students' character. However, forming student character is certainly not an easy thing, it requires continuous struggle to produce results that are in line with national education goals. Social studies learning has similarities with character education in that both have the same goal of making students good citizens, caring about the environment and social problems, and having high responsibility as the color of the country.